The limits of forward guidance - Jeffrey R. Campbell; Filippo Ferroni; Jonas D. M. Fisher; Leonardo Melosi (Federal Reserve Bank of Chicago, 2019)
The viability of forward guidance as a monetary policy tool depends on the horizon over which it can be communicated and its influence on expectations over that horizon. We develop and estimate a model of imperfect central bank communications and use it to measure how effectively the Fed has managed expectations about future interest rates and the influence of its communications on macroeconomic outcomes. Standard models assume central banks have perfect control over expectations about the policy rate up to an arbitrarily long horizon and this is the source of the so-called "forward guidance puzzle." Our estimated model suggests that the Fed's ability to affect expectations at horizons that are sufficiently long to give rise to the forward guidance puzzle is substantially limited. We also find that imperfect communication has a significant impact on the propagation of forward guidance. Finally, we develop a novel decomposition of the response of the economy to forward guidance and use it to show that empirically plausible imperfect forward guidance has a quantitatively important role bringing forward the effects of future rate changes and that poor communications have been a source of macroeconomic volatility.
Keywords: E0; 330; monetary policy; forward guidance puzzle; central bank communication; business cycles; risk management